Optimizing The Production Time of The Max-Plus Time Invariant (SLMI) Linier Algebraic System in The Production of Naziza's Potato Donuts in Padang City - Alda Fuadya; Maya Sari Sahrul (CIB Nusantara, 2025)
In the era of globalization, business development is increasingly high, marked by the emergence of many MSMEs. With the emergence of so many MSMEs, the demands faced by MSME owners are getting higher, which has resulted in increasingly tighter and more competitive competition in the business world. One of them is MSMEs in the culinary sector, Naziza’s Potato Donuts MSME is one of the MSMEs operating in the culinary sector, which is also facing this problem. Naziza’s Potato Donut MSMEs must take various steps to survive, one of which is by improving service. The service that can be provided is fulfilling product orders on time and in the appropriate quantity. Based on this problem, Max-Plus Algebra is expected to be a way to optimize production time in the Naziza’s Potato Donut production system, so that production time can be used effectively and efficiently. Based on the Max-Plus Algebra method, the optimal time for input (entering materials) and time for output (completion of production time) is obtained. So, from the Max-Plus Algebra calculations, the optimal time for MSME production of Naziza’s Potato Donuts is obtained 4 times.